Модернізація управлінських структур підприємств в умовах євроінтеграції - Конащук, Вадим Леонійович; Кравченко, Артем (Економіка та суспільство, 2025)
UKR: У статті розглянуто особливості адаптації управлінських структур українських підприємств до умов європейського ринку в умовах євроінтеграції. Проаналізовано сучасні підходи до управління українських підприємств, а також підходи, що застосовуються в європейських країнах. Проведено порівняльний аналіз управлінських моделей в Україні та Європі, виявлено основні відмінності та спільні риси, що впливають на ефективність управлінських практик. Охарактеризовано поширені моделі управління в європейських країнах, визначено критерії оцінки їх адаптивності до українських умов. Виділено організаційні, економічні, соціальні та культурні критерії для оцінки ефективності впровадження європейських моделей управління в Україні для різних типів організацій, що дозволяє запропонувати конкретні рекомендації для підвищення ефективності управління.

ENG: The article examines the peculiarities of the adaptation of management structures of Ukrainian enterprises to the requirements of the European market in the conditions of European integration. Modern approaches to the management of Ukrainian enterprises are analysed. It was determined that the most common in Ukraine are hierarchical and functional management approaches. Design, matrix and adaptive approaches are used less in the practice of management of Ukrainian companies. Management practices in EU countries are also considered. It is established that European approaches to management are based on decentralization, flexibility, project structures, network models, transparency and accountability. Thanks to this, significant successes in economic development, innovative activity and social cohesion are ensured. For Ukraine, the adaptation of these approaches can become a key factor in overcoming regional disparities, increasing management efficiency, and strengthening competitiveness. A comparative analysis of management models in Ukraine and Europe was conducted; the main differences and common features that affect the effectiveness of management practices were revealed. Common management models in European countries are characterized; criteria for assessing their adaptability to Ukrainian conditions are defined. Organizational, economic, social and cultural criteria for evaluating the effectiveness of the implementation of European management models in Ukraine are highlighted. The choice of these criteria is due to the need to provide a comprehensive analysis of their adaptability, taking into account the peculiarities of management structures, resources, social relations and cultural factors. This allows us to offer specific recommendations for improving management efficiency for various types of organizations. The adaptation of European management standards in Ukraine is an important step towards the integration of national business into the global economic space. The implementation of these standards opens up new opportunities for Ukrainian enterprises, in particular, improving the efficiency of management processes, increasing competitiveness on international markets, and achieving high standards of product and service quality.
Modernization of Management Structures of Enterprises in the Conditions of European Integration
В. Конащук: ORCID 0000-0002-8016-7761; А. Кравченко: ORCID 0009-0009-7404-0156
Keywords: євроінтеграція; управління; адаптація моделей управління; підприємства; європейські стандарти; ефективність управління; еuropean integration; management; adaptation of management models; enterprises; European standards; management efficiency; КМФ; HUMANITIES; HUMANITIES:: Мanagement efficiency